Severe maternal vitamin D deficiency during labor and its correlation with umbilical cord vitamin D level - Yamama Tariq Atta; Shahla Karim Alalaf (Zanco Journal of Medical Sciences)
Background and objective: Prenatal vitamin D insufficiency has been linked to serious negative neonatal outcomes. This study aimed to evaluate the prevalence of vitamin D deficiency in pregnant women and compare maternal and umbilical cord vitamin D levels.